Continuing fascination of exploration in natural substances from microorganisms†. Issue 1 (2nd January 2017) - Takahashi, Yoko
Abstract : In the search for novel organic compounds, I think it is of paramount importance not to overlook the pursuit of microorganism diversity and the abilities those microorganisms hold as a resource. In commemoration of Professor Satoshi Ōmura's Nobel Prize in Physiology or Medicine, I will briefly describe the microorganism that produces avermectin and then discuss how innovating isolation methods and pioneering isolation sources have opened the door to numerous new microorganism resources. Furthermore, as exploratory research of substances views the world from many different angles—from biological activity to a compound's physiochemical properties—it is possible to discover a novel compound from a well-known microorganism. Based on this, I will discuss the future prospects of exploratory research.